Genome-Wide SNP Analysis of Hybrid Clariid Fish Reflects the Existence of Polygenic Sex-Determination in the Lineage - Nguyen, Dung Ho My; Ponjarat, Jatupong; Laopichienpong, Nararat; Panthum, Thitipong; Singchat, Worapong; Ahmad, Syed Farhan; Kraichak, Ekaphan; Muangmai, Narongrit; Duengkae, Prateep; Peyachoknagul, Surin; Na-Nakorn, Uthairat; Srikulnath, Kornsorn (Frontiers in Genetics, 2022)
The African catfish (Clarias gariepinus) may exhibit the co-existence of XX/XY and ZZ/ZW sex-determination systems (SDSs). However, the SDS of African catfish might be influenced by a polygenic sex-determination (PSD) system, comprising multiple independently segregating sex ‘switch’ loci to determine sex within a species. Here, we aimed to detect the existence of PSD using hybrid. The hybrid produced by crossing male African catfish with female bighead catfish (C. macrocephalus, XX/XY) is a good animal model to study SDSs. Determining the SDS of hybrid catfish can help in understanding the interactions between these two complex SDS systems. Using the genotyping-by-sequencing “DART-seq” approach, we detected seven moderately male-linked loci and seventeen female-linked loci across all the examined hybrid specimens. Most of these loci were not sex-linked in the parental species, suggesting that the hybrid exhibits a combination of different alleles. Annotation of the identified sex-linked loci revealed the presence of one female-linked locus homologous with the B4GALNT1 gene, which is involved in the spermatogenesis pathway and hatchability. However, this locus was not sex-linked in the parental species, and the African catfish might also exhibit PSD.